Challenges of Using MR Spectroscopy to Detect Neural Progenitor Cells In Vivo - Dong, Z.; Dreher, W.; Leibfritz, D.; Peterson, B.S. (American Journal of Neuroradiology, 2009)
SUMMARY: A recent report of detection of neural progenitor cells (NPCs) in living human brain by using in vivo proton MR spectroscopy (1H-MR spectroscopy) has sparked great excitement in the field of biomedicine because of its potential influence and utility in clinical neuroscience research. On the other hand, the method used and the findings described in the report also caused heated debate and controversy. In this article, we will briefly detail the reasons for the debate and controversy from the point of view of the in vivo 1H-MR spectroscopy methodology and will propose some technical strategies in both data acquisition and data processing to improve the feasibility of detecting NPCs in future studies by using in vivo 1H-MR spectroscopy.